2018
DOI: 10.17921/1415-6938.2017v21n3p187-193
|View full text |Cite
|
Sign up to set email alerts
|

Potencial Agronômico de Bactérias Endofíticas de Echinodorus scaber Rataj (macrophyllus) em Plântulas de Soja

Abstract: A soja é umas das culturas mais produzidas no mundo, tendo safra na casa dos milhões de toneladas/ano. O aumento na produção dessa cultura permeia o desenvolvimento de tecnologias, que permitam conservar a produtividade e minimizar os dados ambientais oriundos de seu manejo. Uma opção é a inoculação de micro-organismos endofíticos que contribuem com o desenvolvimento dessa cultura. Objetivando averiguar o potencial de produção do fitormônio ácido indol acético (AIA) e solubilização de fosfato de cálcio por bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…These results suggest that SM may result in higher yield and nutritional quality of tomato fruits. According to Joe et al (2012) and Souza et al (2017) the inoculation of endophytic bacteria by the seed microbilization method is the most efficient, besides being economical, safe, reliable and fast (Hallmann et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that SM may result in higher yield and nutritional quality of tomato fruits. According to Joe et al (2012) and Souza et al (2017) the inoculation of endophytic bacteria by the seed microbilization method is the most efficient, besides being economical, safe, reliable and fast (Hallmann et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, studies have shown that soil microorganisms, through the production of organic acids, can accelerate the release of nutrients from these rocks, increasing availability in the soil solution for plant absorption (Moreira;Siqueira, 2006). Several studies have emphasized the selection of phosphate solubilizing microorganisms (Massenssini et al, 2016;Schueler;Dourado;Rizzo, 2019;Terra et al, 2019), and presented promising data on the potential for application in the field (Dabaja et al, 2019;Souza et al, 2017;Terra et al, 2019). Thus, these microorganisms are biotechnological alternatives that can enable the use of natural phosphate from national deposits, such as Araxá and Catalão natural phosphate.…”
Section: Introductionmentioning
confidence: 99%